Confirming The Positive Impact of International Trade Barriers on Enterprises - Zhang, Zheng (Transactions on Economics, Business and Management Research, 2024)
The United States has sanctioned Huawei, making it difficult for the company to continue its development due to the shortage of chips and other essential components. The purpose of this research was to explore the positive impact of international trade barriers on business. The United States sanctioned Huawei for use as a case study. By analyzing the growth of Huawei’s scientific and technological strength, it is evident that the company has increased its R&D investment and adhered to a corporate strategy of independent innovation. Huawei should adhere to scientific and technological innovation, increase investment in research, and cooperate with other scientific and technological enterprises to develop together. By analyzing the success of Huawei’s business layout diversification and localization, Huawei’s business diversification and localization are successful because Huawei restructured its existing business, laid out new industries, and launched products needed by the local market to realize business diversification and localization. Huawei should continuously develop new companies and products to cater to market preferences. By analyzing the effectiveness of Huawei’s efforts to strengthen international exchanges and cooperation and to change its business focus in overseas markets, Huawei has succeeded because it has focused its overseas business on the communications sector, cooperated with operators, and actively sought international cooperation and exchanges. To expand its overseas influence, Huawei should continue to strengthen international exchange, cooperation, and overseas business development.